The Use of Ted Talk Videos in Learning Speaking for EFL Students - Nurul Putri Mawaddah (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
The aims of this study were to find out the influence of speaking skill in using Ted Talk and to describe studentsperception of using Ted Talk in learning speaking. This research was conducted in SMA Unggul Cut Nyak DhienLangsa. The research was quantitative method by using one group pretest-posttest pre-experimental design. To collect the data this research employed questionnaire and test as the instruments. The population of this research was class XII students in SMA Unggul Cut Nyak Dhien Langsa and the sample of this study was 30 students of class XII. The data obtained from the pre-test and post-test was analysed through hypothesis testing by using T-test. The pre-test mean score was 43,8 and the post-test score was 82,5. The result of the T-observed value was 5,2. The result was greater than the t-table value in significance 5%, it was t-table = 2,045 and significance 1% value, t-table = 2,756. Thus, the result fits the criteria t-observed > t-table. Therefore, the alternate Hypothesis was accepted. The Result shows that there was a significance change on students speaking skill score between pre-test and post-test. Apart from that, the results of the questionnaire also stated that learning English using Ted Talk videos is very interesting, convey ideas, improve vocabulary, pronunciation, body language, improve spontaneous speaking skills, and motivate students to learn to speak with Ted Talk. Thus, the results of this study indicate that the use of Ted Talk videos influence students' speaking skills.